[A05] Medium Term Follow up of 254 BeGraft Peripheral Stents Used as Bridging Stents in Fenestrated Endovascular Aneurysm Repair. (November 2022) - Nicholls, Jonathan; Collin, Graham; Collin, Neil; Mezes, Peter; Brooks, Marcus; Bevis, Paul
Abstract : Objective: There are no bridging stents approved for use in fenestrated aortic aneurysm repair (FEVAR). Patency and re-intervention were assessed in the BeGraft Peripheral stent (Bentley InnoMed GmbH), which is now the bridging stent of choice. Methods: Data from consecutive elective patients are collected prospectively in a unit maintained database. All patients with Bentley BeGraft Peripheral bridging stents treated from June 2018 to January 2021 for FEVAR were included. Demographic data, stent specifications, and target vessel diameters were collected. Patients with a minimum 12 month follow up were included. Follow up data collected included mortality, stent patency, and re-intervention, with outcome analysis using the Kaplan–Meier method. Results: Ninety seven patients were included for analysis, with 254 BeGraft peripheral stents used. Median follow up was 24 months (1 – 42 months). The 30 day, one year, and three year patency rates were 100%, 99.1%, and 98%, respectively. Three year freedom from stent re-intervention was 98%. The 30 day, one year, and three year all cause mortality was 2%, 10%, and 24%, respectively. Conclusion: In this study, the use of the BeGraft Peripheral stent for bridging in FEVAR was safe and effective in the short to medium term. BeGraft patency and need for re-bridging stent interventions are comparable with other bridging stents.